2018
DOI: 10.20546/ijcmas.2018.705.039
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Variability, Genetic Divergence and Character Association in Wheat Germplasm of SWRS in Respect of Nutrition and Yield Traits

Abstract: Genetic diversity and the association of the target traits with other traits are the foundation for any crop improvement programme. 308 genotypes of spring wheat reference set (SWRS) were evaluated in simple lattice during crop-season 2015-16 to study genetic diversity and, character association. Phenotypic data were recorded on 15 nutrients and grain yield traits. Analysis of variance revealed significant differences among all the genotypes. The estimates of CV indicated highest variability for agronomic trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This revealed that there was significant genetic variability for yield and yield-related parameters among the genotypes under study and it offers a strong chance of improving traits of interest in wheat breeding program. Kumar et al [18], Berhanu et al [19], Ahmed et al [20], Bhanu [21], Wani et al [22], Kaur et al, [8], Bayisa et al [23] and Sood et al [24], also came to similar conclusions and found that wheat genotypes differed in yield and yield-related characteristics.…”
Section: Dh -Days To 50% Heading Dm-days To Maturity Fw-flag Leaf Wid...mentioning
confidence: 67%
“…This revealed that there was significant genetic variability for yield and yield-related parameters among the genotypes under study and it offers a strong chance of improving traits of interest in wheat breeding program. Kumar et al [18], Berhanu et al [19], Ahmed et al [20], Bhanu [21], Wani et al [22], Kaur et al, [8], Bayisa et al [23] and Sood et al [24], also came to similar conclusions and found that wheat genotypes differed in yield and yield-related characteristics.…”
Section: Dh -Days To 50% Heading Dm-days To Maturity Fw-flag Leaf Wid...mentioning
confidence: 67%
“…Kumar et al (2019) revealed PH had an upper significant positive correlation with EL while negatively correlated with BYP. EL showing a negative correlation with BYP also resulted in many researchers' reports (Burio et al, 2004;Bhushan et al, 2013;Avinashe et al, 2017;Ahmed et al, 2018). BYP has a significant negative correlation with HI.…”
Section: Genotypic and Phenotypic Correlationmentioning
confidence: 71%
“…The values of mean square (MS) for all morpho-agronomic traits showed highly significant differences between sowing seasons of 45 einkorn lines (Table 1). This finding indicates the existence of a high degree of variability in the lines to be exploited in breeding program [28,29]. All of the einkorn lines in the trials flowered well when sown both in autumn and in spring.…”
Section: Morpho-agronomical Traitsmentioning
confidence: 83%